Pengaruh PAD, DAU, DAK, Luas Daerah Terhadap Belanja Modal di kota/kabupaten se Jawa Tengah - Maryati Maryati; Nir Setyo Wahdi; Aprih Santoso (Forum Kerjasama Pendidikan Tinggi, 2022)
This study to analyze and analyze the original Regional Funds, General Allocation Funds, Specific Allocation Funds, and Area Size for Capital Expenditures in cities / districts in Central Java in 2017-2021. The data used are secondary data using a sample of 175 reports from APBD of Cities / regencies throughout Central Java in 2017-2021. This Study uses a census method, namely sampling method by making all participation into a sample. The variables used are regional income (PAD), general allocation funds (DAU), special allocation funds (DAK), and area as independent variables, while capital expenditure as the dependent variable. Data analysis was performed by multiple linear regression analysis using the SPSS 26 program. The results of the study show variable local revenue (PAD) of capital expenditure, will the general allocation funds (DAU), special allocation funds (DAK) and a broad area is not related to the capital expenditure budget allocation.